PENERAPAN METODE FAILURE MODE AND EFFECT ANALYSIS PADA PELAYANAN SEKTOR PUBLIK (STUDI KASUS PASAR TRADISIONAL) - Bukoi, Arismunandar; Sutrisno, Agung; Neyland, Johan S. C. (Jurnal Tekno Mesin, 2024)
Traditional markets are a type of public service that plays a very important role in everyday life. To support the market's strategic role, identification and evaluation of various risk impacts is an important activity for improving market operations for consumer satisfaction. Related to the important functions of the market as mentioned above, this study aims to identify and evaluate the impact of market operational risk using the FMEA method. The study sample was conducted at two traditional markets in Manado City. The results of the study indicate that the mode of operational risk that has an impact on the market is the problem of waste accumulation with an RPN score of 124.16 and market sanitation with an RPN score of 76.13. The two risks with the largest RPN scores are the two market operational risks that are recommended to be addressed by market management immediately. Keywords: Traditional market, risk, risk priority number (RPN). ABSTRAK Pasar tradisional merupakan salah satu jenis tempat pelayanan publik yang sangat berperan dalam kehidupan keseharian. Untuk mendukung peran strategis pasar tersebut, identifikasi dan evaluasi berbagai dampak risiko menjadi aktivitas penting untuk perbaikan operasional pasar demi kepuasan konsumen. Terkait dengan fungsi penting pasar sebagaimana tersebut diatas, penelitian ini bertujuan untuk mengidentifikasi dan mengevaluasi dampak risiko operasional pasar dengan menggunakan metode FMEA. Sampel studi dilakukan pada dua pasar tradisional di Kota Manado. Hasil penelitian mengindikasikan bahwa jenis risiko operasional yang berdampak pada pasar adalah problem penumpukan sampah dengan skor RPN sebesar 124.16 dan sanitasi pasar dengan skor RPN sebesar 76.13. Kedua risiko dengan skor RPN terbesar tersebut merupakan dua risiko operasional pasar yang disarankan segera ditangani manajemen pasar. Kata kunci: Pasar tradisional, risiko, risk priority number (RPN).